The Influence of Audiovisual-Based Health Education Media on Student Attitudes in Conducting First Aid Injuries at SMP Negeri 1 Kalisat - Riswanda Aulia Dityawardani; Feri Ekaprasetia; Rida Darotin (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Background: Injuries often occur in adolescent schoolchildren. There is still a high incidence of injuries, especially in school-age children because it is influenced by several factors, one of which is the attitude of students and people around them who are not right towards first aid in cases of injury. In this case, efforts are needed to form or change the right attitude in order to create appropriate first aid measures as well. The formation or change of attitudes can be done by providing information through interesting and persuasive learning activities, one of which is educational activities, especially in the health sector to increase knowledge and change beliefs that were originally not right (Pangaribu &; Sinuraya, 2022). One method that can be used in health education is the audiovisual-based health education method. Method: This study used a type of quantitative research with an experimental quasy research design with a one group prettest-posttest design approach. The population in this study was grade VII students of SMP Negeri 1 Kalisat with a total of 224 students. The sample in this study was 34 respondents. The sampling technique in this study is a type of proportionate stratified random sampling. Research Results: Based on the results of statistical tests using SPSS with a meaning level of α = 0.05 and using the mc nemar test, a p-value result of 0.000 was obtained, the results showed that the p-value number was smaller than α 0.05. Conclusion: Based on the results of research that has been conducted, it can be concluded that there is an influence of audiovisual-based health education media on students' attitudes in carrying out first aid injuries at SMP Negeri 1 Kalisat.